Determinant Analysis of Early Neonatal Mortality at the Datu Beru Takengon General Hospital, Central Aceh Regency, in 2022 - Barirah Madeni; Sukria; Selvia Zuhra Putri (HM Publisher, 2022)
Background: Attention to efforts to reduce neonatal mortality is important because neonatal mortality contributes to 74% of under-five deaths in Aceh. Of all neonatal mortality, 81% occurred in the 0-6 day age group (early neonates). This study aims to determine the analysis of the determinants of early neonatal mortality at the Datu Beru Takengon General Hospital, Central Aceh Regency. Methods: The research design is an observational case-control approach. 84 case subjects and 84 control subjects were included in this study. Univariate, bivariate, and multivariate data analysis was performed to determine the determinants of early neonatal mortality, p<0.05. Results: Asphyxia increases the risk of premature neonatal mortality by 6.8 times. Low birth weight infants increase the risk of early neonatal by 8.4 times. Prematurity increases the risk of early neonatal mortality by 7.1 times. A parity of more than 3 times increases the risk of early neonatal mortality by 8.9 times, and maternal gestational age of fewer than 20 years increases the occurrence of early neonatal mortality by 14.2 times. Conclusion: Asphyxia, low birth weight, prematurity, parity with risk, and a young mother's gestational age are risk factors that contribute to early neonatal mortality.